Meanings attributed to mental and emotional condition by university students during the COVID-19 pandemic (Research, Society and Development, 2022)
In December 2019 in Wuhan City, China, the genesis of the disease caused by Coronavirus 2019 (COVID-19) was recorded. The evolution of the pandemic condition triggered the need for implementation and intensification of preventive measures allied to disease control and closure of activities, however, due to the inherent need for sectors such as education, there was the suspension of classroom classes and began the implementation of remote education. The university population in general is susceptible to psychological changes due to different factors arising from the academic routine, so the objective of this study was to evidence, through verbalizations, the perception and understanding of the meanings attributed to the mental condition, through self-perception of health in university students, the impact on the continuity of teaching and learning during the pandemic period seeking to understand the real situations experienced by  Same. To this end, a synchronous remote focus group was conducted with engineering students from a federal university of Minas Gerais who signed the Free and Informed Consent Form (TCLE). The results presented showed changes in stress and anxiety levels in students, changes in sleep pattern and difficulties in adapting to the teaching modality. It is noteworthy that the current moment of pandemic was not the genesis of this process, but rather a factor that intensified and analysed the conditions that were raised in this study. Finally, the complexity of this theme and the singularities of each student's situation indicate the need for in-depth attention to the experiences experienced by each individual.